Community Service: Its Use in Criminal Justice - Harris, Robert J. (International journal of offender therapy and comparative criminology, 2002)
Community service has been perceived as a desirable alternative to the use of shortterm imprisonment as a response to increasing crime rates. Although heavily used inWestern Europe and the Old Commonwealth, its adoption in the United States has been localized and patchy. Use in Asia, South America, and Africa is limited. This article reviews the use of community service in selected countries around the world. It concludes that community service can be used as a pretrial diversion, as a condition of probation or parole, or as an option to work off a fine by an impoverished offender. Very often, it is itself a stand-alone sentence, but it can also be used in addition to other sentences. Some countries give community service a secure place in the sentencing tariff, whether as retributively oriented "hard end" penalties or as rehabilitative and/or restorative endeavors. Others leave usage, within broad qualification criteria, to the discretion of sentencers